Comfort and Attitudes Towards Robots Among Young, Middle‐Aged, and Older Adults: A Cross‐Sectional Study. Issue 6 (19th September 2018) - Backonja, Uba; Hall, Amanda K.; Painter, Ian; Kneale, Laura; Lazar, Amanda; Cakmak, Maya; Thompson, Hilaire J.; Demiris, George
Abstract: Purpose: To explore the social impact of, comfort with, and negative attitudes towards robots among young, middle‐aged, and older adults in the United States. Design: Descriptive, cross‐sectional. Conducted in 2014–2015 in an urban area of the western United States using a purposive sample of adults 18 years of age or older. Methods: Respondents completed a survey that included the Negative Attitudes Toward Robots Scale (NARS) and two questions taken or modified from the European Commission's Autonomous System 2015 Report. Analyses were conducted to compare perceptions and demographic factors by age groups (young adults:18–44, middle‐aged adults: 45–64, and older adults: > 65 years old). Findings: Sample included 499 individuals ( n  = 322 age 18–44 years, n  = 50 age 45–64 years, and n  = 102 age 65–98 years). There were no significant differences between age groups for 9 of the 11 items regarding social impact of robots and comfort with robots. There were no significant differences by age groups for 9 of the 14 items in the NARS. Among those items with statistically significant differences, the mean scores indicate similar sentiments for each group. Conclusions: Older, middle‐aged, and younger adults had similar attitudes regarding the social impact of and comfort with robots; they also had similar negative attitudes towards robots. Findings dispel current perceptions that older adults are not as receptive to robots as other adults. This has implications for nurses who integrate supportive robots in their practice. Clinical Relevance: Nurses working in clinical and community roles can use these findings when developing and implementing robotic solutions. Understanding attitudes towards robots can support how, where, and with whom robots can be used in nursing practice.